Pengaruh rasio ekuivalen dan komposisi bahan bakar terhadap karakteristik api dengan menggunakan bahan bakar biodiesel kesambi - Dani Hari Tunggal Prasetiyo; Djoko Wahyudi (Universitas Muhammadiyah Metro, 2022)
The continuous use of fossil energy will cause fossil energy reserves to be depleted. In the transportation and industrial sectors, the use of fossil energy is the main energy source. This is because the fuel used in transportation and industry still relies on fossil fuels. To overcome the energy crisis in the future due to the exploitation of fossil energy, it is necessary to use alternative energy. One alternative energy that can be used is biodiesel. Biodiesel can be obtained from animal or vegetable fats. Kesambi is a plant that has the potential as a biodiesel feedstock. The kesambi plant can produce oil obtained from the seeds of the kesambi fruit through the pressing process. However, before being used and mass produced, a product testing process is required first. Tests can be carried out using the premix combustion method by varying the equivalent ratio and fuel composition. The fuel used is kesambi biodiesel with the addition of methanol. Testing produces fire characteristics. Flame characteristics yielded data on the relationship between laminer combustion rate and equivalent ratio as well as flame height and fuel composition. The test results show that the highest laminer combustion rate lies in the equivalent ratio 1 of 68,024 cm/s with a fuel composition of B90M10. Then the highest flame height at the equivalent ratio of 1.2 is 25,663 mm with a fuel composition of B100M0.